Political Philosophy: A Comparative Analysis of Al-Farabi and Aristotely's Thought - Muhammad Yuslih (Kawanua International Journal of Multicultural Studies, 2022)
Political philosophy is one of the interesting discourses in philosophy. In simple terms, political philosophy is defined as knowledge of various matters relating to politics that are systematic, logical, free, in-depth, and comprehensive. In Western (Greek) philosophers represented by Aristotle, it was because of his success in making concepts in various fields of science, especially about politics. Among Eastern (Islamic) philosophers, Al-Farabi is one of the figures who talks a lot about politics, almost half of the works he writes talk about politics. This paper aims to find common ground and differences in political philosophy thought between Aristotle and Al-Farabi. This research is included in the type of library research. To get the data needed, the authors refer to various sources such as books, journals, articles, and the internet that discuss the thoughts of the two figures. Furthermore, the authors conducted an analysis using the historical-analytical method. The results of this study show that Al-Farabi's political thoughts were inspired and more or less influenced by Aristotle's political thoughts. In addition, it appears that Al-Farabi's political thought is not only oriented to worldly pleasures, but also hereafter. This is influenced by Al-Farabi's belief about the existence of life after death.